GREEN ECONOMY THROUGH DISTILLATION TECHNOLOGY TRANSFER OF CITRONELLA PLANTS ESSENTIAL OILS - Rokiy Alfanaar; Yahya Febrianto; Shesanti Citra Riana; Sudarman Rahman; Awalul Fatiqin; Febri Nur Ngazizah; Karyadi Karyadi; Yudhi Ekakristian Sahari; Mu'afa Purwa Arsana; Thathit Suprayogi (JMM (Jurnal Masyarakat Mandiri), 2023)
Abstrak: Green economy merupakan salah satu jenis ekonomi yang memperhatikan aspek lingkungan. Konsep green economy melibatkan pemanfaatan tanaman sebagai sumber daya terbarukan dalam bidang ekonomi. Sebagai kabupaten yang baru keluar dari status 3T, Seruyan memiliki potensi pengembangan ekonomi dalam bidang green economy. Pengabdian ini bertujuan mengenalkan green economy melalui transfer teknologi destilasi minyak atsiri dengan tanaman yang digunakan adalah Serai Wangi yang lazim ditemukan di Desa Bukit Buluh. Metode pelaksanaan pengabdian terdiri dari merancang alat destilasi dan pelatihan pemanfaatan alat destilasi yang dihadiri 23 peserta dari warga dan pengurus desa dengan peningkatan pemahaman dalam bidang rangkaian distilasi, pemilihan tanaman, dan optimasi ekstraksi sebanyak 95, 60, dan 85 %. Kegiatan pengabdian ini berjalan dengan baik dengan tingginya antusiasme warga dalam kegiatan pelatihan.Abstract: Green economy is an economic model that prioritizes environmental considerations. The concept of the green economy revolves around utilizing plants as renewable resources within the economic sector. Seruyan, recently emerged from 3T status, holds substantial potential for economic growth within the realm of the green economy. The purpose of this initiative is to introduce the principles of a green economy by imparting knowledge about essential oil distillation technology, using Lemongrass as the primary plant source, abundantly available in Bukit Buluh Village. The method of implementing the service consisted of designing distillation equipment and training on the utilization of distillation equipment which was attended by 23 participants from residents and village administrators with an increase in understanding in the fields of distillation circuit, plant selection, and extraction optimization by 95, 60, and 85%. This service activity went well with the high enthusiasm of the residents in the training activities.